2008
DOI: 10.1620/tjem.214.89
|View full text |Cite
|
Sign up to set email alerts
|

Altered Biochemical Parameters in the Saliva of Patients with Breast Cancer

Abstract: Saliva plays an important role in the protection of oral cavity and alterations in either salivary fl ow rate or protein composition may have dramatic effects on oral health. Prevention and management of oral complications of cancer and cancer therapy will improve oral function and quality of life, and reduce morbidity and the cost of care. The aim of this study was to investigate the saliva of patients with breast cancer biochemically and cytologically and compare with healthy controls. Accordingly, lipid per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
10
1
2
Order By: Relevance
“…In OSCC patients without metastasis from the primary tumor, cancer-specific changes in serum and salivary mRNA levels (Li et al 2006; Pickering et al 2007) and blood metabolome levels (Tiziani et al 2009; Zhou et al 2009) were shown. Although this does not constitute direct proof that the aberration in salivary metabolites is attributed to a remote tumor, evidence that the salivary metabolite profiles reflects the systemic and localized tumor status or its response to chemotherapies, such as breast and lung cancer, has accumulated (Emekli-Alturfan et al 2008; Gao et al 2009; Harrison et al 1998; Streckfus et al 2006, 2008). Although previous studies have demonstrated an increase in choline metabolites in blood in various cancers, the increase in choline metabolites in oral cancer patients in study indicate that the transportation of these metabolites from the blood to the saliva through the salivary gland is low, even though their levels in blood are elevated.…”
Section: Resultsmentioning
confidence: 97%
“…In OSCC patients without metastasis from the primary tumor, cancer-specific changes in serum and salivary mRNA levels (Li et al 2006; Pickering et al 2007) and blood metabolome levels (Tiziani et al 2009; Zhou et al 2009) were shown. Although this does not constitute direct proof that the aberration in salivary metabolites is attributed to a remote tumor, evidence that the salivary metabolite profiles reflects the systemic and localized tumor status or its response to chemotherapies, such as breast and lung cancer, has accumulated (Emekli-Alturfan et al 2008; Gao et al 2009; Harrison et al 1998; Streckfus et al 2006, 2008). Although previous studies have demonstrated an increase in choline metabolites in blood in various cancers, the increase in choline metabolites in oral cancer patients in study indicate that the transportation of these metabolites from the blood to the saliva through the salivary gland is low, even though their levels in blood are elevated.…”
Section: Resultsmentioning
confidence: 97%
“…There is considerable evidence that the hormone replacement therapy is more strongly associated with the risk of some invasive breast carcinomas (3). The incidence of breast cancer in 2007 may have decreased from previous decades but among women worldwide breast cancer is the most common cause of cancer death (4,5). Attention to breast cancer screening, risk assessment and risk reduction strategies is necessary to eradicate breast cancer and the deaths it causes (4).…”
Section: Introductionmentioning
confidence: 99%
“…Saliva plays an important role in the protection of oral cavity and alterations in either salivary flow rate or protein composition may have dramatic effects on oral health. Diagnosis of diseases via the analysis of saliva is potentially valuable since collection of the saliva is associated with fewer compliance problems as compared with the collection of blood samples (5). Three biomarkers that have been reported to be linked with breast cancer are C-erbB-2, CEA and CA15-3.…”
Section: Introductionmentioning
confidence: 99%
“…Saliva is increasingly used and well validated in diagnosing. Moreover, saliva is reported to be suitable to detect the body's oxidative stress level (1)(2)(3)(4). GSH is present in saliva, cerebrospinal fluid, sweat, seminal fluid, and milk.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress constitutes the basis for many diseases and it may account for the severity of systemic and oral disease complications. Salivary-reduced glutathione (GSH) and lipid peroxidation (LPO) have been suggested to be used to detect the oral oxidant-antioxidant status (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%